Building a digital agronomy and soil hub for Ghana - Jizorkuwie, Abdul-latif Baamonyor; Yeboah, Patricia Amankwaa; Masoud, Jalaludeen; Ofosu-ampong, Kingsley; Abera, Wuletawu (2026)
Soil degradation and inefficient fetilizer use limit agricultural productivity in Ghana. To address this, the Alliance of Bioversity International and CIAT is partnering with other agriculture and research institutions in developing a digital agronomy and soil hub to deliver location-specific fertilizer recommendations. Using the AgWise workflow, the initiative integrates soil, crop, climate, and agronomy datasets to develop location-specific fertilizer recommendations. District-level recommendations have been generated and are being tested with farmers, showing improved performance over blanket guidelines.